Sustainable Ceramics: Creating Effective Key Performance Indicators for Industry Monitoring - Sharma Manni; Vani V. Divya; Helena Raj J. Vijilius; Dutt Amit; Kumar J. Sunil; Almusawi Muntather; Gupta Nakul; Goyal Rajesh (E3S Web of Conferences)
Sustainable development in the ceramic industry focuses on meeting present needs without compromising future resources. Key strategies include recycling waste, improving energy efficiency, and adopting green technologies. The materials used in creating ceramics, which are very abundant and renewable, are primarily sand or clay, unlike other materials such as real wood. This means that ceramic products are already environmentally friendly right from the start, before the manufacturing process commences. This study discusses environmentally sustainable recycled concrete, using ceramic waste as coarse aggregate in construction. It also discussed how the energy efficiency of buildings can be optimized through thermal energy storage and environmentally friendly materials. This also examined the analysis of Energy Management Systems (EMS) and how they can promote sustainability. The industry is changing with technological innovation using alkali- activated mortars, porous ceramics, and low-carbon technologies. In all their challenges of high energy consumption, green technologies and sustainable practices are crucial in lowering carbon footprints and promoting environmental responsibility. The focus has been made towards the various applications of the ceramic materials in different areas and the benefits associated with them. It can be concluded that the with better technological advancements and research on the design aspects, there is high scope of performance enhancement in the industrial areas.